Actor roles in co-production—Introducing intermediaries: Findings from a systematic literature review - Nathalie Haug (Public Administration, 2023)
Public service ecosystems are used to understand how multiple actors co-produce public services and create public value. Especially interactions between public service providers and service users are essential. However, systematic examinations of these interactions and what roles the different actors play are rare. This study closes this gap by conducting a systematic literature review with three main findings. First, public service providers play an important role: they facilitate co-production by micromanaging or facilitating collaboration, empowering service users, and translating the results of the process back into the organization. Second, service users contribute to co-production by providing resources. Third, a new category of actors is proposed: the co-production intermediary. Intermediaries are formal organizations whose primary role is to support service providers in service delivery. This study comprehensively analyzes the different actors and power constellations between them.
Keywords: 340